2016
DOI: 10.1097/sga.0000000000000188
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Irritable Bowel Syndrome Among Healthcare Personnel

Abstract: This study aims to investigate the frequency of irritable bowel syndrome (IBS) among healthcare professionals. A total of 394 healthcare professionals and 207 individuals who were selected as a control group were included in the study. A questionnaire form containing Rome III diagnostic criteria was administered to health workers and the control group. The study groups were evaluated according to age, gender, occupation, profession, presence of chronic disease, drug usage, smoking, awareness of IBS, alarm symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 28 publications
4
21
1
1
Order By: Relevance
“…The prevalence of IBS in this study was found to be 14.5%. The finding is relatively consistency with findings among medical students in Saudi Arabia, Iran and health care professionals in Turkey where the prevalence of IBS was 13.7%, 12.6% and 13.5% respectively (9,11,12). On the contrary, studies in Asia; Pakistan and China reported high prevalence of IBS among medical students 28.3% and 33.3% respectively whilst prevalence of 28.4% among health care professionals.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The prevalence of IBS in this study was found to be 14.5%. The finding is relatively consistency with findings among medical students in Saudi Arabia, Iran and health care professionals in Turkey where the prevalence of IBS was 13.7%, 12.6% and 13.5% respectively (9,11,12). On the contrary, studies in Asia; Pakistan and China reported high prevalence of IBS among medical students 28.3% and 33.3% respectively whilst prevalence of 28.4% among health care professionals.…”
Section: Discussionsupporting
confidence: 85%
“…On the contrary, a study in Saudi Arabia among medical students IBS was predominant in males however, age and advanced academic levels were predictors of IBS (12). Studies in Turkey, Pakistan and Nigeria among health care professionals have displayed similar findings with studies among medical students in China where being a female was associated with IBS (9,10,17).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…IBS was more common in healthcare professionals than in the control group. Healthcare workers are more disposed to IBS because International Journal of Clinical Medicine of their stressful working environment [20]. Well-being at work has been revealed to be predisposed by job features and personal variances in coping styles.…”
Section: Discussionmentioning
confidence: 99%